Exploring Financial Management Behavior of Higher Education Students in South Kalimantan - Asiah, Antung Noor; Nastiti, Rizky; Syahdan, Saifhul Anuar; Akbar, Masithah (Asosiasi Dosen Akuntansi Indonesia, 2025)
In this technologically advanced world, it is essential for students to develop the competence to manage their financial behavior, especially in the context of utilizing financial technology applications for effective financial decision-making. This study examines the effects of financial education, digital financial management, and lifestyle on the Financial Management Behavior of higher education students in South Kalimantan. Employing a quantitative research methodology, data were collected through a structured survey administered to 132 economics major students across the region. The results indicate that financial education exerts a significant positive influence on students’ financial planning, saving, and budgeting behaviors. However, digital financial literacy, while positively associated with increased financial control and decision-making efficiency, in this study demonstrates no statistically significant influence on Financial Management Behavior. Moreover, lifestyle factors, particularly consumption habits and social norms, are found to have an effect on Financial Management Behavior. These findings underscore the multifaceted nature of financial behavior among young adults and highlight the critical role of educational and technological interventions in promoting sound financial practices within the context of higher education in South Kalimantan.